2020
DOI: 10.1371/journal.pone.0234361
|View full text |Cite
|
Sign up to set email alerts
|

Motion sickness symptoms during jumping exercise on a short-arm centrifuge

Abstract: Artificial gravity elicited through short-arm human centrifugation combined with physical exercise, such as jumping, is promising in maintaining health and performance during space travel. However, motion sickness symptoms could limit the tolerability of the approach. Therefore, we determined the feasibility and tolerability, particularly occurrence of motion sickness symptoms, during reactive jumping exercises on a short-arm centrifuge. In 15 healthy men, we assessed motion sickness induced by jumping exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Different types of exercise that target not only the cardiovascular system but also muscle and bone would probably be more suitable, for example the high-intensity jump training that proved to be very effective in maintaining muscle, bone and cardiovascular health in a previous long-term bed rest study (Kramer et al 2017a ). It was already demonstrated that jumping whilst being centrifuged is possible, albeit with reduced peak ground reaction forces and changes in the movement pattern that might lower the countermeasure efficacy (Dreiner et al 2020 ; Kramer et al 2020a ; Frett et al 2020 ). Hence, future studies are needed to (a) determine those exercise regimes that could be combined with AG exposure, and (b) disentangle the effects observed in studies combining centrifugation and exercise by comparing the effects of the combined intervention to the effects of exercise alone.…”
Section: Discussionmentioning
confidence: 99%
“…Different types of exercise that target not only the cardiovascular system but also muscle and bone would probably be more suitable, for example the high-intensity jump training that proved to be very effective in maintaining muscle, bone and cardiovascular health in a previous long-term bed rest study (Kramer et al 2017a ). It was already demonstrated that jumping whilst being centrifuged is possible, albeit with reduced peak ground reaction forces and changes in the movement pattern that might lower the countermeasure efficacy (Dreiner et al 2020 ; Kramer et al 2020a ; Frett et al 2020 ). Hence, future studies are needed to (a) determine those exercise regimes that could be combined with AG exposure, and (b) disentangle the effects observed in studies combining centrifugation and exercise by comparing the effects of the combined intervention to the effects of exercise alone.…”
Section: Discussionmentioning
confidence: 99%
“…Early work with AG higher than 1 g suggested that movement during rotation precipitates disorientation and/or motion sickness ( Bertolini and Straumann, 2016 ) due to cross-coupled angular acceleration and induction of Coriolis forces ( Bertolini and Straumann, 2016 ), in addition to orthostatic intolerance ( Goswami et al, 2015 ). In case the g load is moderate (e. g. 1 g at CoM) and the exercise-related head and body motion is congruent, moderate movement appears well tolerated ( Frett et al, 2020b ). Indeed, plyometric exercises such as jumping can be performed during SAHC, albeit requiring familiarization to generate reaction forces equivalent to ground conditions ( Frett et al, 2020b ; Kramer et al, 2020b ; Dreiner et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Artificial gravity generated through a short arm centrifuge could be beneficial in attenuating the physiological deterioration in weightlessness [111]. Yet, artificial gravity alone may not suffice [49].Combinations of artificial gravity and exercise training hold promise [112]. During the Neurolab mission, four out of six crew members were exposed to 1 g on a centrifuge installed inside the Space Shuttle Columbia.…”
Section: Potential Orthostatic Intolerance Countermeasures For Space ...mentioning
confidence: 99%